Composite ceramic
By combining a composite oxide phase of alumina particles, zirconia particles and Si in the composite ceramics and forming a specific contact portion, the problem of insufficient deformation of the existing ceramics is solved, and high deformation and high strength ceramics are achieved.
Patent Information
- Application Number
- CN202380066859.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-29
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-25
AI Technical Summary
The existing composite ceramics have shortcomings in deformability and are difficult to achieve high deformability.
The deformation ability of the ceramic is improved by combining alumina particles and zirconia particles in the composite ceramic and forming a specific contact portion on its surface, combining the composite oxide phase of Si.
It achieves high deformation properties of ceramics, has good bending ability, and maintains high strength and high destructive toughness.
Smart Images

Figure CN119894845A_ABST
Abstract
Description
Technical Field
[0001] An embodiment of the present invention relates to a composite ceramic. Background Art
[0002] Composite ceramics containing a plurality of ceramic particles having different main components are known. For example, the present applicant has previously proposed a sintered body containing alumina particles and zirconia particles as a composite ceramic having high strength and toughness (see Patent Document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent document 1: International Publication No. 2006 / 080473. Summary of the invention
[0006] A composite ceramic according to one embodiment of the present invention comprises a plurality of alumina particles, a plurality of zirconia particles, and a composite oxide phase of Si. The plurality of alumina particles include prismatic particles. The plurality of zirconia particles include spherical particles. The composite ceramic comprises particles having a first contact portion in which the prismatic particles and the spherical particles are in contact with each other at a portion of their surfaces. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 This is a cross-sectional view showing an example of the composite ceramic according to the embodiment.
[0008] Figure 2 This is a graph showing the relationship between the aspect ratio and the frequency of aluminum oxide particles included in the composite ceramic. DETAILED DESCRIPTION
[0009] In the above-mentioned composite ceramics, for example, deformability is lacking, and there is room for improvement.
[0010] Therefore, it is desired to provide a highly deformable composite ceramic.
[0011] Hereinafter, embodiments of the composite ceramic disclosed in the present application will be described with reference to the accompanying drawings. It should be noted that the present invention is not limited to the embodiments described below.
[0012] Figure 1 1 is a cross-sectional view showing an example of a composite ceramic according to an embodiment. Figure 1 As shown, the composite ceramic 1 of the embodiment includes a plurality of alumina particles 10 , a plurality of zirconium oxide particles 12 , and a composite oxide phase 14 of Si.
[0013] The composite ceramic 1 includes prismatic particles among a plurality of alumina particles 10. The prismatic particles are particles containing alumina as a main component. Hereinafter, they may be referred to as prismatic alumina particles 10.
[0014] The composite ceramic 1 includes particles having a contact portion where a portion of the surface of the prismatic alumina particles 10 and the spherical zirconia particles 12 are in contact with each other. Here, the contact portion may be referred to as a first contact portion 12A.
[0015] Here, the contact portion refers to a portion where a portion of the spherical zirconia particle 12 is in contact with a portion of the surface of the prismatic alumina particle 10. In this case, contact means that it has nothing to do with the bonding force between a portion of the alumina particle 10 and a portion of the zirconia particle 12. For example, it includes a state where a portion of the alumina particle 10 and a portion of the zirconia particle 12 are displaced even under a low load, and a state where a portion of the alumina particle 10 and a portion of the zirconia particle 12 are sintered and are unlikely to be displaced. In these cases, it is preferred that the Si composite oxide phase 14 exists around a portion of the alumina particle 10 and a portion of the zirconia particle 12.
[0016] As the Si composite oxide phase 14, in addition to glass represented by borosilicate glass, aluminum silicate and zircon can be cited. Preferably, at least one of borosilicate glass, aluminum silicate and zircon exists in the Si composite oxide phase 14. Hereinafter, the Si composite oxide phase 14 is sometimes referred to as the composite oxide phase 14.
[0017] According to such a structure, it is possible to obtain ceramics that are easily deformed. In other words, it is possible to obtain composite ceramics 1 that are easily bent.
[0018] Here, the fact that the composite ceramic 1 is easily deformed or easily bent means that the deformation capacity when the composite ceramic 1 is deformed from the initial shape is large. The deformation capacity refers to, for example, the change in the position of the load point obtained by performing a three-point bending test on a test piece of the composite ceramic 1. The change refers to the deformation of the test piece of the composite ceramic 1 within the range of elastic deformation. The deformation capacity of the composite ceramic 1 refers to the maximum value of the deformation within the range that does not damage the test piece, but here, as described later, since it is carried out simultaneously with the three-point bending test, for convenience, the change refers to the change when the test piece breaks when the test piece is subjected to the three-point bending test.
[0019] The composite ceramic 1 is easily deformable because the alumina particles themselves are difficult to bend, but the composite ceramic 1 contains the alumina particles 10 and the easily elastically deformable zirconium oxide particles 12. The composite ceramic 1 contains the Si composite oxide phase 14, which is also one of the reasons why the composite ceramic 1 is easily deformable.
[0020] In the composite ceramic 1, the Si composite oxide phase 14 exists in the region except the alumina particles 10 and the zirconia particles 12. In other words, the Si composite oxide phase 14 exists around the alumina particles 10 and the zirconia particles 12.
[0021] Since the Si composite oxide phase 14 exists adjacent to the alumina particles 10 and the zirconia particles 12 , the Si composite oxide phase 14 weakens the restraining force between the alumina particles 10 , between the zirconia particles 12 , and between the alumina particles 10 and the zirconia particles 12 in the composite ceramic 1 .
[0022] The composite ceramic 1 has a property of being easily deformed because the composite ceramic 1 includes the prismatic alumina particles 10 and the spherical zirconia particles 12 and is a combination of these two particles.
[0023] In the case of the composite ceramic 1, a crystal structure in contact with the spherical zirconia particles 12 is formed on the surface of the prismatic alumina particles 10. In this case, since the zirconia particles 12 are spherical, a portion of the surface of the spherical zirconia particles 12 is in contact with the surface of the prismatic alumina particles 10. In other words, the prismatic alumina particles 10 and the spherical zirconia particles 12 are in contact with each other only in a small area.
[0024] In the composite ceramic 1, since the prismatic alumina particles 10 and the spherical zirconia particles 12 are in contact with each other only in a small area, it is considered that the restraining force between the prismatic alumina particles 10 and the spherical zirconia particles 12 is small and they are in a state of being easy to move relative to each other. Since the prismatic alumina particles 10 and the spherical zirconia particles 12 are in contact with each other in such a small area, the restraining force between the particles of both parties becomes small. In this case, the ratio of the surface contact between the zirconia particles 12 and the alumina particles 10 is preferably in the range shown below.
[0025] For example, when observing the cross section of the composite ceramic 1, the length of the surface of the aluminum oxide particle 10 that is in contact with the zirconium oxide particle 12 (the length of the side formed when observed in the photograph) is set to L1, and on the other hand, the length of the contact surface between the aluminum oxide particle 10 and the zirconium oxide particle 12 (the length of the side formed when viewed in cross section) is set to L2, and the ratio (L2 / L1) is preferably 1% or more and 10% or less. As a result, it becomes difficult for the aluminum oxide particle 10 and the zirconium oxide particle 12 to be excessively constrained by the two particles. In this case, a plurality of zirconium oxide particles 12 may be in contact with one surface (side) of one aluminum oxide particle 10.
[0026] In addition, in the case where the zirconium oxide particles 12 and the aluminum oxide particles 10 are considered to be in contact with each other, the Si composite oxide phase 14 may be thinly interposed between the aluminum oxide particles 10 and the zirconium oxide particles 12. The thickness of the Si composite oxide phase 14 in this case is preferably 0 μm or more and 1 μm or less, and particularly preferably 0.5 μm or less.
[0027] On the contrary, when both alumina particles 10 and zirconia particles 12 are prismatic and have more side surfaces in contact with each other, the contact area between alumina particles 10 and zirconia particles 12 increases, so the restraining force between the two increases.
[0028] The composite ceramic 1 exhibits the property of being easily deformed because, first, the crystal structure includes zirconium oxide particles 12; includes alumina particles 10 constituting a prismatic shape and spherical zirconium oxide particles 12; and the spherical zirconium oxide particles 12 and the alumina particles 10 constituting a prismatic shape are in contact with each other at a portion of their surfaces.
[0029] The range in which the spherical zirconia particles 12 are in contact with the prismatic alumina particles 10 may be 1 to 20, or 1 to 10, when the length of the outline of the spherical zirconia particles 12 is 100.
[0030] The composite ceramic 1 is preferably a dense body. Here, "dense body" means a body having a porosity of 5% or less. The porosity of the composite ceramic 1 can be calculated from the result of observing a cross section of the composite ceramic 1 with a scanning electron microscope (SEM).
[0031] In measuring the porosity of the composite ceramic 1, for example, the following method is preferably used. First, a predetermined area of the cross section of the composite ceramic 1 is set, and the total area of pores present in the predetermined area is calculated. Then, the porosity is calculated by dividing the total area of pores by the predetermined area of the cross section.
[0032] Although repeatedly described, the plurality of alumina particles 10 include prismatic particles. Here, "prismatic" refers to a situation in which, when a cross section of the composite ceramic 1 is observed using an SEM, the cross section becomes a longitudinally long polygonal shape. The polygonal shape means that when the cross section of the alumina particle 10 is observed, at least two long sides and two short sides can be observed in its outline. In this case, the two long sides and the two short sides can be configured to be opposite to each other. The two long sides do not need to be parallel to each other. The two short sides do not need to be parallel to each other. A portion of the long side can also be bent at a small angle, and the portion forms a portion of the polygon. From the appearance, as long as it has the above-mentioned structure and is considered to be prismatic, a portion of the long side can also be partially bent.
[0033] The aspect ratio of the alumina particles 10 may be 1.5 or more, and may be 2 or more. In this case, the aspect ratio of the alumina particles 10 is preferably 3 or less because the composite ceramic 1 can be densified.
[0034] The cross section of the composite ceramic 1 is observed using a SEM, and the aspect ratio of the alumina particles 10 is determined from the image (photograph). At this time, whether the particles appearing in the imaged area are alumina particles 10 or zirconia particles 12 is identified using Energy Dispersive X-ray Spectroscope (EDS).
[0035] Specifically, first, a photograph of about 10 to 20 alumina particles 10 identified by EDS analysis is selected. Then, the length L1 of the longest diameter of each alumina particle 10 present in the selected photograph is measured. Then, for the alumina particle 10 for which L1 is measured, the length L2 at a right angle to the center of L1 is measured. Then, the ratio of L1 to L2 (L1 / L2) is calculated. L1 / L2 is the aspect ratio.
[0036] When the aspect ratio of the alumina particles 10 is large, that is, when the alumina particles 10 have an elongated shape, the spherical zirconia particles 12 are easily arranged on the side surfaces of the alumina particles 10 , so that a highly deformable composite ceramic 1 is easily obtained.
[0037] Here, the average particle size of the aluminum oxide particles 10 when the prismatic aluminum oxide particles 10 are also included may be 0.5 μm or more and 3 μm or less. In this case, the average particle size of the aluminum oxide particles 10 is the average value ((L1+L2) / 2) of the length L1 and the length L2 used in the calculation of the aspect ratio. The average particle size of the aluminum oxide particles 10 is obtained by measuring all the aluminum oxide particles 10 included in the photographs of about 10 to 20 aluminum oxide particles 10.
[0038] The area ratio per unit area of the prismatic aluminum oxide particles 10 included in the plurality of aluminum oxide particles 10 may be 5% or more and 10% or less.
[0039] The plurality of zirconium oxide particles 12 include spherical particles. Here, "spherical" means that when a cross section of the composite ceramic 1 is observed using an SEM, 80% or more of the entire outline of the zirconium oxide particle 12 includes a curved portion.
[0040] In addition, for the spherical zirconia particles 12, in addition to the condition that the portion having a curved shape is 80% or more, the aspect ratio is preferably 1.1 or less. In this case, in the composite ceramic 1, it is preferred that, in addition to the state in which the aluminum oxide particles 10 and the zirconia particles 12 are in contact with each other at a portion of their surfaces, there is also a portion in which a plurality of zirconia particles 12 are in contact with each other at a portion of their surfaces. In other words, the plurality of zirconia particles 12 preferably include zirconia particles 12 having second contact portions 12B in which the zirconia particles 12 are in contact with each other at a portion of their surfaces.
[0041] Regarding the second contact portion 12B, when the length of the outline of the spherical zirconia particle 12 located on one side is 100, the range where the spherical zirconia particles 12 are in contact with each other is about 1 to 20 of the length of the outline, and in particular, about 1 to 10.
[0042] In addition, the zirconium oxide particles 12 that are in contact with the prismatic alumina particles 10 at a portion of their surfaces may be only spherical zirconium oxide particles 12, or may be quasi-spherical zirconium oxide particles 12 described later. Alternatively, both the spherical zirconium oxide particles 12 and the quasi-spherical zirconium oxide particles 12 may be in contact with the prismatic alumina particles 10 at a portion of their surfaces.
[0043] Since the elastic modulus of the zirconium oxide particles 12 is originally lower than that of the aluminum oxide particles 10, the composite ceramic 1 becomes easier to deform if there is a portion where a plurality of zirconium oxide particles 12 are connected with each other in a small area. In this case, for the composite ceramic 1, it is preferred that three aluminum oxide particles 10 exist in contact with each other, and one or more spherical zirconium oxide particles 12 are in contact with any one of the three aluminum oxide particles 10. In this case, it is preferred that the three aluminum oxide particles 10 include one or more prismatic aluminum oxide particles 10.
[0044] Furthermore, in the composite ceramic 1, when the surface of the prismatic alumina particle 10 is divided into the end face f1 and the side face f2, preferably, the first contact portion 12A is more present on the side face f2 than on the end face f1. Here, when observing the cross section of the alumina particle 10, the end face f1 of the prismatic alumina particle 10 is a portion corresponding to the short side. On the other hand, when observing the cross section of the alumina particle 10, the side face f2 of the prismatic alumina particle 10 is a portion corresponding to the long side. In addition, one or more spherical zirconium oxide particles 12 may be present per unit area of the alumina particles 10 including three prismatic alumina particles 10.
[0045] In other words, the plurality of zirconium oxide particles 12 may have portions in point contact with the surface of the aluminum oxide particle 10. Here, "in point contact" means that the zirconium oxide particle 12 is in contact with other particles within 20%, within 10%, and particularly within 5% of the length of the contour of the zirconium oxide particle 12.
[0046] The average particle size of the zirconium oxide particles 12 including the spherical and quasi-spherical zirconium oxide particles 12 is preferably 0.7 μm or more and 1 μm or less. In this case, the average particle size of the zirconium oxide particles 12 is calculated using the average value ((L1+L2) / 2) of the length L1 and the length L2 used in the calculation of the aspect ratio, as in the case of the aluminum oxide particles 10. The average particle size of the zirconium oxide particles 12 is determined by measuring all the zirconium oxide particles 12 included in a photograph of about 10 to 20 aluminum oxide particles 10.
[0047] The Si composite oxide phase 14 is a grain boundary phase containing the alumina particles 10 and the zirconia particles 12. The Si composite oxide phase 14 may also contain a small amount of a crystalline phase. As long as the properties such as the deflection amount, fracture toughness, and three-point bending strength of the composite ceramic 1 can be set to a predetermined value or more, the Si composite oxide phase 14 is preferably contained in a ratio that is distributed around the alumina particles 10 and the zirconia particles 12. In this case, the ratio of the Si composite oxide phase 14 is preferably 1% or more and 7% or less in terms of area ratio.
[0048] The Young's modulus of the alumina particles 10, the zirconia particles 12, and the composite oxide phase 14 of Si are different from each other. Specifically, the Young's modulus increases in the order of the composite oxide phase 14 of Si < zirconia particles 12 < alumina particles 10. As described above, in the composite ceramic 1 of the embodiment, the contact area between the zirconia particles 12 and the alumina particles 10 with a high Young's modulus is small. In addition, around the alumina particles 10 and the zirconia particles 12, there is a composite oxide phase 14 of Si having a lower Young's modulus than them. Thus, a composite ceramic 1 with a large deflection and high deformation can be obtained. Here, "high deformation" means that when a test piece with a width of 10 mm and a thickness of 0.05 mm is subjected to a three-point bending strength test, the deflection is 0.5 mm or more relative to a span of 10 mm. According to a specific example, the deflection of the composite ceramic 1 is preferably 0.7 mm or more.
[0049] In addition, the fracture toughness of the composite ceramic 1 can be 3.5 MPa·√m or more, and in particular, can be 3.8 MPa·√m or more. In addition, the three-point bending strength of the composite ceramic 1 can be 750 MPa or more, and in particular, can be 800 MPa or more. Thus, a high-strength composite ceramic 1 can be obtained. The composite ceramic 1 has a fracture toughness of 3.5 MPa·√m or more, a three-point bending strength of 750 MPa or more, and has a deformation capacity of a deflection of 0.7 mm or more.
[0050] In this case, the mass ratio of the aluminum oxide particles 10 contained in the composite ceramic 1 is preferably 60% or more and 85% or less.
[0051] The mass ratio of the zirconium oxide particles 12 contained in the composite ceramic 1 is preferably 20% or more and 40% or less.
[0052] The mass ratio of the Si complex oxide phase 14 contained in the composite ceramic 1 is preferably 2.4% or more and 4.8% or less.
[0053] In addition, when the content ratios of the alumina particles 10, the zirconia particles 12, and the Si composite oxide phase 14 contained in the composite ceramic 1 are converted into volume, the volume fraction of the alumina particles 10 is preferably 70% to 75%, the volume fraction of the zirconia particles 12 is preferably 18% to 23%, and the volume fraction of the Si composite oxide phase 14 is preferably 4% to 11%. In this case, the density of the alumina particles 10 is 4 g / cm 3 The density of the zirconium oxide particles 12 is 6 g / cm 3 The density of the Si composite oxide phase 14 is 2 g / cm 3 .
[0054] The composite ceramic 1 includes, in addition to alumina particles 10 as a first phase and zirconia particles 12 as a second phase, a third phase consisting of a composite oxide phase 14 of Si in a ratio of 4% to 11% by volume, thereby becoming a composite ceramic having high strength and easy bending properties.
[0055] Furthermore, when the ratio of the alumina particles 10, the zirconium oxide particles 12, and the Si composite oxide phase 14 constituting the composite ceramic 1 is expressed as an area ratio, it is as follows.
[0056] The area ratio per unit area of the alumina particles 10 and the zirconia particles 12 contained in the composite ceramic 1 is preferably 40% to 60% for the alumina particles 10 and 30% to 40% for the zirconia particles 12. The remaining portion of the Si composite oxide phase 14 is preferably 5% to 20%.
[0057] In addition, it is preferable that the Si composite oxide phase 14 contains alkaline earth elements (Mg, Ca) in addition to Si. In this case, Si and the alkaline earth elements are contained in the form of oxides.
[0058] The ratio of the alumina particles 10, the zirconium oxide particles 12, and the Si composite oxide phase 14 contained in the composite ceramic 1 can be determined by, for example, ICP (Inductively Coupled Plasma) analysis. The ratio of the alumina particles 10 is obtained by converting aluminum (Al) into Al2O3 from among the multiple elements that can be confirmed by ICP analysis.
[0059] Similarly, zirconium (Zr) is converted into ZrO 2 from among a plurality of elements that can be confirmed by ICP analysis as the ratio of the zirconium oxide particles 12 .
[0060] If the remaining elements are Si, Mg, and Ca, for example, Si, Mg, and Ca are converted into SiO 2 , MgO, and CaO, respectively, and the total amount of these three components becomes the remaining content in the composite ceramic 1 .
[0061] Then, the total amount of the aluminum oxide particles 10 , the zirconium oxide particles 12 , and the remainder in terms of their respective proportions is taken as the total amount (100% by mass) of the composite ceramic 1 .
[0062] Then, the content of the remainder is obtained by subtracting the content of the aluminum oxide particles 10 and the zirconium oxide particles 12 from the total amount, and the content of the remainder is obtained as the content of the composite oxide phase 14 of Si.
[0063] The components contained in the Si composite oxide phase 14 can be detected using an analyzer (Energy Dispersive X-ray Spectroscope: EDS) attached to an electron microscope. The electron beam diffractometer attached to an electron microscope can determine that the Si composite oxide phase 14 is amorphous (glass).
[0064] In addition, the relative dielectric constant of the composite ceramic 1 may be lower than that of zirconia. Specifically, the relative dielectric constant of the composite ceramic 1 may be greater than 9 and less than 15. By making the relative dielectric constant of the composite ceramic 1 lower than that of zirconia, for example, when the composite ceramic 1 is used as a substrate for mounting a component, the electrical characteristics of the mounted component are less likely to deteriorate.
[0065] As described above, the plurality of zirconium oxide particles 12 include spherical particles. However, in this case, the spherical shape is not limited to a shape close to a perfect circle.
[0066] Spherical means a shape in which the ratio D2 / D1 is greater than or equal to 0.8 and less than or equal to 1 when the longest diameter D1 of the cross section of the zirconium oxide particle 12 and the length D2 in the direction perpendicular to the longest diameter are measured. In this case, for example, zirconium oxide particles 12 having a cross-sectional shape close to a hexagon or an octagon may be included. In other words, particles having a quasi-spherical shape may be included. Here, "quasi-spherical particles" means that when the cross section of the composite ceramic 1 is observed using an SEM, the aspect ratio is greater than 1.1 and less than 1.2, and the curved portion of the entire contour of the zirconium oxide particle 12 is greater than or equal to 50% and less than or equal to 70%.
[0067] Here, a spherical shape may be referred to as a quasi-spherical shape. The composite ceramic 1 may include spherical zirconium oxide particles 12 and zirconium oxide particles 12 constituting a quasi-spherical shape.
[0068] In addition, the plurality of zirconium oxide particles 12 may include a portion where a portion of the surface of the plurality of zirconium oxide particles 12 is in contact with each other. The portion where a portion of the surface of the plurality of zirconium oxide particles 12 is in contact with each other is sometimes referred to as a second contact portion. In other words, there may be a portion where the plurality of zirconium oxide particles 12 are in point contact with each other.
[0069] (Example)
[0070] Samples No. 1 to 6 were prepared and their characteristics were evaluated.
[0071] First, alumina powder, zirconia powder and glass powder were mixed at a predetermined ratio, and sintered at a predetermined sintering condition (temperature) to obtain a sintered body. The ratios of alumina particle powder, zirconia powder and glass powder and the sintering temperatures in sample numbers 1 to 6 are shown in Table 1.
[0072] As the Si composite oxide powder, a mixed powder of SiO2, CaO (raw material: CaCO3) and MgO (talc) was used. The mass ratio of SiO2, CaO (raw material: CaCO3) and MgO (talc) in the mixed powder was 3:1:1.
[0073] As the mixed powder, a powder having an average particle size larger than the average particle size of the alumina powder was used. When the average particle size of the alumina powder was set to 1, the average particle size of the mixed powder was 1.3 times. The average particle size of CaCO3 was twice the average particle size of SiO2. The average particle size of MgO was four times the average particle size of SiO2. The average particle size of the zirconium oxide powder was 0.17 times the average particle size of the alumina powder when the average particle size was set to 1.
[0074] Specifically, raw material powders having the following average particle sizes were used: an average particle size of 1.4 μm for alumina powder, an average particle size of 0.24 μm for zirconium oxide powder, an average particle size of 1.06 μm for SiO2 powder, an average particle size of 2.0 μm for CaO (CaCO3), and an average particle size of 4.16 μm for MgO (talc).
[0075] It should be noted that the results of the composition analysis showed that the samples after sintering all had the same composition as the formulated composition. Atomic absorption analysis and ICP analysis were used in the composition analysis. In addition, the porosity of the samples after sintering was less than 2%, and they were dense bodies.
[0076] Table 1
[0077]
[0078] Table 2 shows the results of observing the cross sections of the sintered bodies of Sample Nos. 1 to 6. Sample Nos. 1 to 6 are samples produced under the conditions shown in Table 1, respectively.
[0079] First, composite ceramics 1 were identified from the prepared samples by the following method: a rectangular region having about 10 to 20 alumina particles 10 was identified, and the main components of the particles present in the region were identified using EDS to distinguish alumina particles 10 from zirconia particles 12 .
[0080] Then, the length L1 of the longest diameter of each alumina particle 10 present in the selected photograph and the length L2 in the perpendicular direction thereof were measured to obtain the aspect ratio and the average particle size. The aspect ratio was obtained from the ratio of L1 / L2. The average particle size was obtained from (L1+L2) / 2.
[0081] SEM observation of the sintered bodies of the composite ceramics 1 of Sample Nos. 1 to 6 revealed that all of the samples were sintered bodies containing prismatic alumina particles 10. The sintered bodies of the composite ceramics 1 of Sample Nos. 1 to 6 contained alumina particles 10 having an aspect ratio of 1.5 or more.
[0082] The following items were evaluated for the zirconium oxide particles 12. The items evaluated were the shape of the zirconium oxide particles 12, the ratio of the number of particles that were spherical among the plurality of zirconium oxide particles 12, the ratio of the curved portions (ratio of the contour length) among the zirconium oxide particles 12 that were determined to be spherical particles, the aspect ratio, the average particle size, and the ratio of the number of positions that indicated the state of the first contact portion.
[0083] The aspect ratio and average particle size were evaluated using the same method as for alumina particles 10. The number of zirconium oxide particles 12 determined to be spherical was divided by the total number of all zirconium oxide particles 12 present in the region to determine the number ratio of spherical particles in zirconium oxide particles 12.
[0084] Here, the spherical shape of the zirconium oxide particles 12 means that the aspect ratio of all the zirconium oxide particles 12 measured is 1.1 or less, and the ratio of the length of the curved portion in the outline of the zirconium oxide particles 12 is 80% or more. The quasi-spherical shape of the zirconium oxide particles 12 means that the aspect ratio of all the zirconium oxide particles 12 measured is greater than 1.1 and less than 1.2, and the ratio of the length of the curved portion in the outline of the zirconium oxide particles 12 is 50% or more and 70% or less.
[0085] As shown in Table 2, the sintered bodies of the composite ceramics 1 prepared in Sample Nos. 1 to 5 were all sintered bodies containing spherical particles and quasi-spherical particles.
[0086] The number ratio of the positions showing the state of the first contact portion 12A was determined by visual counting from the photographs of the above evaluation. It should be noted that among the prepared samples, the sintered bodies of the composite ceramics 1 of sample numbers 1 to 5 all included the second contact portion 12B where a plurality of zirconium oxide particles 12 were in contact with each other at a portion of their surfaces.
[0087] For the aluminum oxide particles 10 and the zirconium oxide particles 12, the area of the entire region of the photograph used in the above evaluation is set as A0, and the total area of the aluminum oxide particles 10 and the area of the zirconium oxide particles 12 is set as A1, and the area ratio of the Si composite oxide phase 14 is calculated by (A0-A1) / A0.
[0088] Table 2
[0089]
[0090] Table 3 shows the results of measuring the characteristics of sample numbers 1 to 6 and evaluating the suitability. The flexure test for measuring the deflection amount was performed simultaneously with the three-point bending strength test. Specifically, a test sample was cut out from the prepared sample, and when the three-point bending strength test was performed, the change from the flat state when the test sample was broken was taken as the deflection amount. The dimensions of the test sample were approximately L = 20 mm, W = 4 mm, and t = 50 μm.
[0091] The fracture toughness of each sample was measured by the indentation method (IF method) specified in JIS R1607-1995. In this case, a sample having a thickness of 2 mm was prepared separately from the above-mentioned measurement sample.
[0092] In Table 3, samples with particularly good applicability were evaluated as ◎, samples with good applicability were evaluated as ○, and samples with inapplicability were evaluated as ×. It should be noted that in the above three-level evaluation, ◎ and ○ were evaluated as satisfying the criteria of composite ceramic 1.
[0093] Table 3
[0094]
[0095] Samples 1 to 5 have a deflection of 0.5 mm or more and high deformation. Sample 6, on the other hand, has a higher fracture toughness and three-point bending strength than samples 1 to 5, but a deflection of less than 0.5 mm and poor deformability.
[0096] Sample No. 6 does not include spherical or quasi-spherical zirconium oxide particles 12 as the zirconium oxide particles 12 .
[0097] In sample numbers 1 to 3 and 5, the area ratio of the aluminum oxide particles 10 is 60% or more and 70% or less, and the area ratio of the zirconium oxide particles 12 is 30% or more and 40% or less.
[0098] In sample numbers 1, 3, and 5, the ratio of the number of zirconium oxide particles 12 forming the first contact portion 12A was 16% or more.
[0099] In the sintered bodies of the composite ceramics of Sample Nos. 1 to 5, a portion where one or more spherical zirconium oxide particles 12 were in contact with any of the three alumina particles 10 that were in contact with each other was observed.
[0100] In the sintered bodies of the composite ceramics of Sample Nos. 1 to 5, when the surfaces of the prismatic alumina particles 10 are divided into end faces and side faces, the first contact portions are more present on the side faces than on the end faces.
[0101] Figure 2 This is a graph showing the relationship between the aspect ratio and the frequency of aluminum oxide particles included in the composite ceramic. Figure 2 The case of sample No. 1 is shown as an example of composite ceramics.
[0102] With respect to the alumina particles, when the aspect ratio is taken as the horizontal axis and the frequency (number) is taken as the vertical axis, the composite ceramic of the present invention has two groups with different aspect ratios. Figure 2 As shown, the aluminum oxide particles have a group of two peaks having different aspect ratios.
[0103] In this case, the composite ceramic was identified from the prepared sample by the following method: A rectangular region having about 70 to 100 alumina particles was identified, and the main component of the particles present in the region was identified using an analyzer (EDS) attached to an electron microscope, thereby identifying the alumina particles.
[0104] Next, the length L of the major axis and the length S of the minor axis of the alumina particles were determined from the electron microscope photograph. The minor axis crossed the major axis at right angles to the major axis, and their ratio (L / S) was determined as the aspect ratio of the alumina particles.
[0105] In this case, the figure is plotted with the interval of the aspect ratio set to 0.1. In the figure, a first group with an aspect ratio of 1.3 or more and 2.2 or less and a second group with an aspect ratio of 2.6 or more and 2.8 or less are shown. In this evaluation, when the aspect ratio is 0.2 or more, the groups have different aspect ratios.
[0106] Therefore, in the figure, even if the frequency of the range of aspect ratio greater than 1.6 and 1.7 or less is 0, the range of aspect ratio less than 1.5 and the range greater than 1.7 are not considered as a group with different aspect ratios.
[0107] In addition to sample number 1, for sample numbers 2 and 5, the relationship between the aspect ratio and its frequency is also as follows: Figure 2 Two different groups of samples as shown.
[0108] For the samples No. 1, No. 2, and No. 5, the deflection amount was 0.81 mm or more.
[0109] The reason why there are two groups with different aspect ratios in the graph showing the relationship between the aspect ratio of aluminum oxide particles and its frequency is that a powder having an average particle size larger than that of aluminum oxide powder is used as the mixed powder, and further, the composition of the aluminum oxide powder, zirconium oxide powder and the mixed powder composed of a composite oxide of Si is adjusted as shown in Table 1.
[0110] In one embodiment, (1) a composite ceramic, wherein:
[0111] The composite ceramic has a composite oxide phase of a plurality of aluminum oxide particles, a plurality of zirconium oxide particles and Si.
[0112] The plurality of aluminum oxide particles include prismatic particles,
[0113] The plurality of zirconium oxide particles include spherical particles,
[0114] The composite ceramic includes particles having a first contact portion in which the prismatic particles and the spherical particles are in contact with each other through a portion of their surfaces.
[0115] (2) In the composite ceramic of (1) above, the plurality of zirconium oxide particles may include zirconium oxide particles having a second contact portion in which the zirconium oxide particles are in contact with each other at a portion of their surfaces.
[0116] (3) In the composite ceramic of (1) or (2) above, the aspect ratio of the alumina particles may be 1.5 or more.
[0117] (4) In the composite ceramic described in any one of (1) to (3) above, one or more of the spherical particles may be in contact with any one of the three alumina particles that are in contact with each other.
[0118] (5) In the composite ceramic described in any one of (1) to (4) above, when the surface of the prismatic particle is divided into an end face and a side face, the first contact portion may be more present on the side face than on the end face.
[0119] (6) In the composite ceramic described in any one of (1) to (5) above, the Si composite oxide phase may be present in a region other than the alumina particles and the zirconia particles.
[0120] The Si composite oxide phase may be present at an area ratio of 1% to 7% per unit area.
[0121] (7) In the composite ceramic described in any one of (1) to (6) above, the alumina particles may include two groups having different aspect ratios.
[0122] (8) In the composite ceramic described in any one of (1) to (7) above, the aluminum oxide particles may be greater than 60 mass % and less than 85 mass %, the zirconium oxide particles may be greater than 20 mass % and less than 40 mass %, and the composite oxide phase of Si may be greater than 2.4 mass % and less than 4.8 mass %.
[0123] (9) In the composite ceramic described in any one of (1) to (8) above, the volume fraction of the aluminum oxide particles can be greater than 70% and less than 75%, the volume fraction of the zirconium oxide particles can be greater than 18% and less than 23%, and the volume fraction of the Si composite oxide phase can be greater than 4% and less than 11%.
[0124] Those skilled in the art can easily derive further effects or other modes. Therefore, the broader aspects of the present invention are not limited to the specific details and representative embodiments shown and described above. Therefore, various changes can be made without departing from the spirit or scope of the concept of the overall invention defined by the appended claims and their equivalents.
[0125] Description of Reference Numerals
[0126] 1: Composite ceramics;
[0127] 10: Alumina particles;
[0128] 12: Zirconia particles;
[0129] 12A: first contact portion;
[0130] 12B: second contact portion;
[0131] 14: Composite oxide phase of Si.
Claims
1. A composite ceramic, wherein: The composite ceramic has a composite oxide phase of a plurality of aluminum oxide particles, a plurality of zirconium oxide particles and Si. The plurality of aluminum oxide particles include prismatic particles, The plurality of zirconium oxide particles include spherical particles, The composite ceramic includes particles having a first contact portion in which the prismatic particles and the spherical particles are in contact with each other through a portion of their surfaces.
2. The composite ceramic according to claim 1, wherein: The plurality of zirconium oxide particles include zirconium oxide particles having a second contact portion in which the zirconium oxide particles are in contact with each other at a portion of their surfaces.
3. The composite ceramic according to claim 1 or 2, wherein: The aspect ratio of the alumina particles is greater than 1.
5.
4. The composite ceramic according to any one of claims 1 to 3, wherein One or more of the spherical particles are in contact with any one of the three aluminum oxide particles that are in contact with each other.
5. The composite ceramic according to any one of claims 1 to 4, wherein When the surface of the prismatic particle is divided into an end face and a side face, the first contact portion is more present on the side face than on the end face.
6. The composite ceramic according to any one of claims 1 to 5, wherein The Si composite oxide phase exists in a region other than the alumina particles and the zirconia particles, The Si composite oxide phase is present at an area ratio of 1% to 7% per unit area.
7. The composite ceramic according to any one of claims 1 to 6, wherein The aluminum oxide particles include two groups having different aspect ratios.
8. The composite ceramic according to any one of claims 1 to 7, wherein The aluminum oxide particles account for 60 mass % to 85 mass % both inclusive, the zirconium oxide particles account for 20 mass % to 40 mass % both inclusive, and the Si composite oxide phase accounts for 2.4 mass % to 4.8 mass % both inclusive.
9. The composite ceramic according to any one of claims 1 to 8, wherein The volume fraction of the aluminum oxide particles is 70% to 75%, the volume fraction of the zirconium oxide particles is 18% to 23%, and the volume fraction of the Si composite oxide phase is 4% to 11%.
Citation Information
Patent Citations
Composite ceramic and method for producing same
WO2006080473A1